PENGARUH KEPEMIMPINAN YANG MELAYANI TERHADAP PERILAKU KERJA INOVATIF DENGAN JOB CRAFTING DAN OTONOMI KERJA SEBAGAI VARIABEL PEMEDIASI (Studi pada Karyawan PT Nelta Multi Gracia) - Faishal Zuhair Bimo Dewantoro; Amie Kusumawardhani (Diponegoro Journal of Management, 2023)
ABSTRACTThis study aims to examine the effect of Servant Leadership on Innovative Work Behaviormediated by Job Crafting and Job Autonomy on employees of PT Nelta Multi Gracia.The saturation sampling method was used to determine the number of research samples, namelyall employees of PT Nelta Multi Gracia. The analytical technique used is path analysis with the SPSS:25program to determine the path coefficient and the effect of the independent variable on the dependentvariable.The results showed that Servant Leadership had a positive and significant effect on InnovativeWork Behavior. Servant Leadership has a positive and significant effect on Job Crafting. ServantLeadership has a positive and significant effect on Job Autonomy. Job Crafting has a positive andsignificant effect on Innovative Work Behavior. Job Autonomy has a positive and significant effect onInnovative Work Behavior. This study also shows that Job Crafting and Job Autonomy can mediate theeffect of Servant Leadership on Innovative Work Behavior